2014
DOI: 10.1002/ajh.23882
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine in combination with mycophenolate mofetil versus methotrexate for graft versus host disease prevention in myeloablative HLA‐identical sibling donor allogeneic hematopoietic cell transplantation

Abstract: Graft-versus-host disease (GVHD) remains a major cause of morbidity and mortality in allogeneic hematopoietic cell transplantation (HCT) despite current prophylaxis. Methotrexate (MTX) with a calcineurin inhibitor (CNI) is the current standard, however, has several toxicities. Mycophenolate mofetil (MMF) is frequently used in reduced-intensity HCT, but data in myeloablative transplants is limited. We thus retrospectively identified 241 patients who underwent myeloablative HCT from an HLA-identical sibling dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 38 publications
3
29
0
1
Order By: Relevance
“…The use of ATG could impair the early development of donor‐derived T cells due to the persistence of these antibodies in the patient for several weeks after administration especially if given too close to graft infusion 11. Similarly, use of MTX is also associated with delayed engraftment and increased risk of graft failure 14, 15. Reducing the intensity of the GVHD prophylaxis regimen by avoiding the use of ATG and MTX will relatively “protect” the naïve T cells from the toxicity of these two drugs and achieved a higher rate of engraftment 29.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of ATG could impair the early development of donor‐derived T cells due to the persistence of these antibodies in the patient for several weeks after administration especially if given too close to graft infusion 11. Similarly, use of MTX is also associated with delayed engraftment and increased risk of graft failure 14, 15. Reducing the intensity of the GVHD prophylaxis regimen by avoiding the use of ATG and MTX will relatively “protect” the naïve T cells from the toxicity of these two drugs and achieved a higher rate of engraftment 29.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have compared the outcomes between CBT with or without ATG, and the use of ATG was associated with lower OS and higher NRM, regardless of the lower incidence of GVHD 12, 13. Similarly, use of MTX‐containing regimen for GVHD prophylaxis has been associated with delayed engraftment and increased risk of graft failure in patients with hemoglobinopathies and malignant diseases transplanted with an HLA‐identical sibling CB unit 14, 15…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A cochrane database systemic review in 2014 showed that a combination of MMF/calcineurine inhibitor compared to MTX/ci showed a more favorable toxicity profile (66). Multiple studies in 2015 showed that a higher dose of Mycophenolate Mofetil reduced aGVHD in Ric double umbilical cord blood transplants.…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…In contrast, we previously presented, in abstract form, our retrospective experience with MMF in myeloablative sibling donor transplantations (n ¼ 114), with an incidence of grade II to IV acute GVHD of 34% and severe grades III and IV GVHD of 12%, and 3-year nonrelapse mortality of 25%. Only 15% and 21% of deaths were attributed to acute and chronic GVHD, respectively [3], compared with the 49% of deaths related to GVHD reported in Al-Kadhimi's study [1].…”
mentioning
confidence: 43%